Agroprotein som fodermedel till slaktkyckling - Wallström, Emily (SLU/Dept. of Animal Nutrition and Management (until 231231), 2012)

(untitled)
Destillers dried grains with soluble (DDGS) is a by-product when producing ethanol. DDGS from wheat has a high crude protein content and a good amino acid profile, which makes it an interesting feed ingredient for poultry. The disadvantage of feeding DDGS from wheat to poultry is that it also contains a high fiber content that chickens don’t have the ability to break down. Lantmännen Agroetanol has developed a new protein feedstuff from DDGS by extracting wheat protein from DDGS, the product name is Agroprotein SD. Unlike DDGS Agroprotein contains a smaller proportion of insoluble fiber but still has a good amino acid profile, making the product in theory better suited to poultry than DDGS. The present project aims to examine how Lantmännen Agroetanol’s new product, Agroprotein serve as a feed ingredient in different inclusion levels for broiler chickens and how it affects chickens’ productivity and health. The objectives are also to study the effects on growth, feed intake, feed conversion ratio, ileal digestibility, dry matter of manure (DM), litter quality, cleanliness of plumage, foot condition, sex determination and mortality. The study included 140 day-old chicks of the hybrid ROSS 308. The chicks were randomly divided into 20 cages with seven chickens per pen in a climate-controlled house. Four different inclusion levels of Agroprotein (0, 4, 8 and 12 %) were used and each treatment was randomly divided over five cages. Each week the live weight, feed intake and feed conversion ratio was registered group wise in the different groups. During the experiment various health parameters were examined such as, sticky droppings and dry matter in manure. The animals were slaughtered on day 35 and live weight, sex, plumage cleanliness and foot injuries recorded was registered individually. The ileal digestibility was measured by picking out the intestinal contents (from Meckel's divertikulum to 4 cm proximal to the ileocecal junction). The samples were sent for analysis at the laboratory of Animal Science at Ultuna Research Center. The study revealed no significant differences in growth rate over the complete production period between treatments. There were no significant differences in feed intake or feed conversion ratio after the first week. The results from the digestibility study were similar between treatments, suggesting that there was no difference in the chickens' ability to digest the protein regardless of the inclusion level of Agroprotein in the diets. Average digestibility of Agroprotein was 58.8 %. The study showed that the chickens had an increased tendency for foot injury at a higher inclusion of Agroprotein. The litter was dry throughout the production period, but increased inclusion of Agroprotein in the diet made the litter more compressed. The results of DM determination showed significant differences between the treatments on day 10, the chickens that consumed feed with Agroprotein had generally a higher DM compared to the control chickens. The DM determination on day 33 was confirmed. However, with an increased inclusion of Agroprotein in the diet there is a risk of increase foot injuries and compressed litter. That might be due to a lower DM of manure that this study showed on day 10. Another possible explanation is the low digestibility of Agroprotein. During the production process of Agroprotein the drying can cause Maillard reactions. The proteins denatures from it´s natural state when they are heated that makes them hard for chickens to digest and absorb in the intestine. The conclusion of this study is that Agroprotein can safely be incorporated in chicken diets up to 4 % without affecting production or health parameters. Further studies are needed to confirm the results from the current study.